Let Sleeping Dogs Lie : (3z(BSister(3y (BJane #9 /s - Brown, Rita Mae; Gildea, Lee, Jr. (New York : Ballantine Books, 2014)
scene and gallops through to the very surprising end."--Horse Illustrated The Hounds and the Fury "An intriguing story."--Associated Press"--.
"On the Ides of March, an ill wind blows no good -- especially when it knocks down a tree limb in the oldest equine graveyard in America, revealing remains that are decidedly un-equine. It falls to Master of the Foxhunt, the indomitable "Sister" Jane Arnold and her trusty hounds to investigate an old murder with present day repercussions. To start off, the complicated relations between three old families and their prize thoroughbreds must be untangled. And when Sister's troublesome nemesis Crawford Howard sticks his nose in, she must make a difficult choice. Someone has killed and will kill again to keep a dark secret, but Sister Jane is not one to let sleeping dogs lie.."--
scene and gallops through to the very surprising end."--Horse Illustrated The Hounds and the Fury "An intriguing story."--Associated Press"--
Keywords: Arnold, Jane (Fictitious character) -- Fiction; Murder -- Investigation -- Fiction; Fox hunting -- Fiction; FICTION / Mystery & Detective / General; FICTION / Suspense; FICTION / Humorous; Virginia -- Fiction; Mystery fiction; Suspense fiction